From Black Phosphorus to Phosphorene: Basic Solvent Exfoliation, Evolution of Raman Scattering, and Applications to Ultrafast Photonics. (21st October 2015) - Guo, Zhinan; Zhang, Han; Lu, Shunbin; Wang, Zhiteng; Tang, Siying; Shao, Jundong; Sun, Zhengbo; Xie, Hanhan; Wang, Huaiyu; Yu, Xue‐Feng; Chu, Paul K.
Abstract : Although phosphorene has attracted much attention in electronics and optoelectronics as a new type of two‐dimensional material, in‐depth investigations and applications have been limited by the current synthesis techniques. Herein, a basic N ‐methyl‐2‐pyrrolidone (NMP) liquid exfoliation method is described to produce phosphorene with excellent water stability, controllable size and layer number, as well as in high yield. Phosphorene samples composed of one to four layers exhibit layer‐dependent Raman scattering characteristics thus providing a fast and efficient means for the in situ determination of the thickness (layer number) of phosphorene. The linear and nonlinear ultrafast absorption behavior of the as‐exfoliated phosphorene is investigated systematically by UV–vis–NIR absorption and Z‐scan measurements. By taking advantage of their unique nonlinear absorption, ultrashort pulse generation applicable to optical saturable absorbers is demonstrated. In addition to a unique fabrication technique, our work also reveals the large potential of phosphorene in ultrafast photonics. Abstract : A basic N ‐methyl‐2‐pyrrolidone liquid exfoliation method is described to produce phosphorene with an excellent water stability, controllable size and layer number, as well as in a high yield. Phosphorene with one to four layers exhibits layer‐dependent Raman scattering characteristics thus providing a fast and efficient means for the in situ determination of the thickness of phosphorene.